LoRaWAN para comunicações de redes elétricas inteligentes em áreas suburbanas e rurais - Silva, Flavio Eduardo Soares e (2019)
The Smart Grid, as a concept of monitored and controlled elements in the generation, transmission, distribution and use of electric energy, allows efficient and distributed energy resources to be operated in real time. This communication between various devices present in the smart grid and from these with the supervisory systems, such as the Advanced Distribution Management System (ADMS), is necessary to deploy an appropriate communication network to meet the requirements of all the components of this smart grid. Considering the characteristics of smart grids, a rural area brings greater challenges and requires the study of the implementation of this technology. A problem encountered in smart grid design and deployment of the communication network that will serve the project. Many ways to develop communication network projects have been tested in Brazil, all in urban areas where the cellular network is abundant and the service points are close to each other. Those considerations motivated the development of this master thesis that presents the methodology elaborated to assist in the decision making process for the adoption of a LoRaWAN communication network and the minimal requirements to operate such communication network considering rural areas. The work was developed and tested in an experimental network LORAWAN installed in the Campus of the Federal University of Santa Maria (UFSM) and in a case study carried out in a rural area of southern Brazil. The results were satisfactory to the use of the LoRaWAN network for applications in smart grid works to meter and, in the future, automate the distribution network.